A multistate demographic model for firms in the province of Gelderland - Corina Huisman; Leo Van Wissen (European Regional Science Association (ERSA), 2004)
In the last two decades researchers from various disciplines have made attempts to model and estimate developments in the size and structure of the population of firms. Although these attempts give useful insights into possible explanatory factors of firm dynamics, the explanatory value, and hence predictive power of these models is usually not very high. In this paper we follow a pure demographic approach for the modelling of firm survival. Important dimensions of the firm are firm age, firm size (in number of employees), economic activity and firm location. Using empirical firm level data for the region of Gelderland in the Netherlands over the period 1986-2002, developments in survival are described and analysed over time in an age-period-cohort perspective. In a later phase of the project, these (aggregated) scenarios will serve as a point of reference for comparisons to more extended model specifications using micro-simulation that include additional explanatory and spatial variables. Keywords: demography of the firm, Age-Period-Cohort model, firm survival, closures
Keywords: 330; demography of the firm; Age-Period-Cohort model; firm survival; closures